The right to privacy and personal data protection in the age of new technologies - Kucharczyk, Krystian; Joachymczyk, Paweł (Scientific Journal of Bielsko-Biala School of Finance and Law, 2021)
The issue of the existence of the right to privacy and the related right to protection of personal data is so wide in the modern world that it prompts an analysis of the regulation in this area. The last decades have brought a significant development of new technologies, having a huge impact on our lives. It is linked to two industrial revolutions: the third (scientific and technological) and the fourth (digital). The biggest change facing the individual is the process of digitisation of social life. The possibilities of new devices are constantly increasing in terms of reception, data processing and also automation. With this progress, a significant part of everyday duties has been transferred to the virtual sphere. Taking this into account, the topic of this work is limited to issues related to ICT technologies, which influence people directly and indirectly on a daily basis. This is mainly due to the fact that an individual constantly interacts with such technologies, for example in the form of mobile phones, computers or the Internet. This is shown by a report prepared by the National Debt Register, according to which, even before the pandemic, as many as 80% of Poles spent more than one hour a day in front of a screen, and one in four spent more than three hours. Furthermore, almost half of Poles use e-banking, and among the five activities they do most frequently using their phones, as many as three relate strictly to the Internet